Improving analytical reasoning and argument understanding: a quasi-experimental field study of argument visualization. (December 2018) - Cullen, Simon; Fan, Judith; van der Brugge, Eva; Elga, Adam
Abstract The ability to analyze arguments is critical for higher-level reasoning, yet previous research suggests that standard university education provides only modest improvements in students' analytical-reasoning abilities. What pedagogical approaches are most effective for cultivating these skills? We investigated the effectiveness of a 12-week undergraduate seminar in which students practiced a software-based technique for visualizing the logical structures implicit in argumentative texts. Seminar students met weekly to analyze excerpts from contemporary analytic philosophy papers, completed argument visualization problem sets, and received individualized feedback on a weekly basis. We found that seminar students improved substantially more on LSAT Logical Reasoning test forms than did control students (d = 0.71, 95% CI: [0.37, 1.04], p < 0.001), suggesting that learning how to visualize arguments in the seminar led to large generalized improvements in students' analytical-reasoning skills. Moreover, blind scoring of final essays from seminar students and control students, drawn from a parallel lecture course, revealed large differences in favor of seminar students (d = 0.87, 95% CI: [0.26, 1.48], p = 0.005). Seminar students understood the arguments better, and their essays were more accurate and effectively structured. Taken together, these findings deepen our understanding of how visualizations support logical reasoning and provide a model for improving analytical-reasoning pedagogy. Short heading: Argument-visualization training leads to improved reasoning skills The ability to analyze arguments is critical for higher-level reasoning, yet previous research suggests that standard university education provides only modest improvements in students' analytical reasoning abilities. What pedagogical approaches are most effective for cultivating these skills? We investigated the effectiveness of a 12-week undergraduate seminar in which students learned to visualize the logical structures implicit in argumentative texts. We found that students who completed this seminar improved substantially more on LSAT Logical Reasoning test forms than did control students, showing that this intervention produced generalized improvements in analytical reasoning skills. Moreover, seminar students wrote more accurate and effectively structured final essays than did control students. Taken together, these findings deepen our understanding of how visualizations support logical reasoning and provide a model for improving analytical reasoning pedagogy.